Efficacy and safety of intravenous thrombolysis for acute ischemic stroke within 3–4.5 hours in Lithuania - VILIONSKIS, Aleksandras; KNOKNERIENĖ, Olga; JATUŽIS, Dalius (Acta medica Lituanica, 2012)
Background. Intravenous thrombolysis has been shown as an appropriate treatment for stroke patients within 3–4.5 hours from the onset of stroke in randomized and observational studies, yet extended therapeutic window remains off-label in routine clinical setting. The aim of our study was to evaluate the efficacy and safety of intravenous thrombolysis within 3–4.5 hours for acute stroke patients in Lithuania.Methods. In this pair-matched case control study stroke patients treated by intravenous thrombolysis during January 2002 – May 2010 were included. The patients were divided into two groups according to onset-to-needle time (0–180 min. (group I), and 181–270 min. (group II)), and were pair-matched 1 : 1 according to age and stroke severity. The primary end-point was good functional status after 3 months. Mortality and rates of life-threatening bleeding and symptomatic intracranial hemorrhage were used for analysis of safety profile.Results. 28 pairs were included in the final analysis. The mean onset-to-needle time was significantly higher in group II. There was no difference between the groups according to baseline variables. 32.1% of patients in group I and 39.3% of patients in group II had good functional status (p = 0.58) after 3 months. No significant differences were found between the groups in the safety profile, however, the rate of symptomatic intracerebral hemorrhage was higher in group I.Conclusions. Intravenous thrombolysis within 3–4.5 h after the onset of stroke is acceptable and effective treatment for acute ischemic stroke in our routine clinical setting. Further studies are needed to assess the reasons of higher rates of symptomatic intracerebral hemorrhage.
Keywords: acute stroke therapy; thrombolysis; rtPA; efficacy; safety; time window